A thermal–hydromechanical coupled model for poro-viscoplastic saturated freezing soil. Issue 9 (4th July 2022) - Weng, Xiaolin; Sun, Yufeng; Yang, Zhuang; Wang, Deng; Yu, Hangfei
Abstract: Most existing thermal–hydromechanical (THM) models used to describe the process of frost heave assumed the freezing soil to be elastic. However, an inelastic constitutive model capable of reflecting the viscous constitutive behaviour of freezing soils should be considered. Based on the existing mathematical model, this study presented an improved mathematical model of coupled water, heat, and stress for saturated freezing soil, in which the soil was assumed to be elastic-viscoplastic and its viscoplasticity was modelled by means of a simple (linear) Norton–Hoff's law. In addition, solid–fluid interface energy was considered to formulate the effective water and ice pressures and liquid–crystal equilibrium condition which can be used to explain the micro-cryosuction mechanism was adopted to replace Clapyron equation which were used in most existing models. To solve the nonlinear governing equations, numerical simulations were performed using COMSOL software. Finally, the improved model was validated by comparing its simulation results with reference model and the distribution curves of frost heave, temperature, water content and flux rate were discussed.